Polarization and Strain in Piezoelectric Nanomaterials: Advancing Sensing Applications in Biomedical Technology - Anmol Garg; Sajal Agarwal; Deepak Punetha (IEEE Open Journal of Nanotechnology)
This paper reports the comparative analysis of different piezoelectric materials through a MEMS-based piezoelectric actuator model, emphasizing their potential for sensing applications. The polarization and electrostrictive strain tensor capabilities have been extensively studied for different piezoelectric materials such as PZT, LiNbO3, PVDF, etc. The simulation results obtained at varying voltages and mechanical stress demonstrate that LiNbO3 exhibits superior performance among the tested materials, with a polarization value of 0.5163 C/m2 at 800 volts and an electrostrictive strain tensor of 0.01 at an applied mechanical stress of 25 MPa. These findings will assist scientists in selecting the most suitable piezoelectric materials for sensing applications in biomedical fields.